Room-Temperature Gas Sensors Under Photoactivation: From Metal Oxides to 2D Materials - Kumar, Rahul; Liu, Xianghong; Zhang, Jun; Kumar, Mahesh (Nano-micro letters, 2020)
Highlights Operations of metal oxide semiconductors gas sensors at room temperature under photoactivation are discussed. Emerging two-dimensional (2D) materials-based gas sensors under light illumination are summarized. The advantages and limitations of metal oxides and 2D-materials-based sensors in gas sensing at room temperature under photoactivation are highlighted. Room-temperature gas sensors have aroused great attention in current gas sensor technology because of deemed demand of cheap, low power consumption and portable sensors for rapidly growing Internet of things applications. As an important approach, light illumination has been exploited for room-temperature operation with improving gas sensor’s attributes including sensitivity, speed and selectivity. This review provides an overview of the utilization of photoactivated nanomaterials in gas sensing field. First, recent advances in gas sensing of some exciting different nanostructures and hybrids of metal oxide semiconductors under light illumination are highlighted. Later, excellent gas sensing performance of emerging two-dimensional materials-based sensors under light illumination is discussed in details with proposed gas sensing mechanism. Originated impressive features from the interaction of photons with sensing materials are elucidated in the context of modulating sensing characteristics. Finally, the review concludes with key and constructive insights into current and future perspectives in the light-activated nanomaterials for optoelectronic gas sensor applications.